2019
DOI: 10.1055/s-0039-1693695
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor versus Cesarean Delivery in Twin Pregnancies

Abstract: Objective This study was aimed to compare maternal and neonatal outcomes between women with twin pregnancies who underwent induction of labor with those women who had planned Cesarean delivery (CD). Study Design This is a retrospective cohort study of women with twin pregnancies ≥ 24 weeks with an indication for delivery but not in labor. Two groups were examined, women who underwent induction and women who underwent planned CD. Maternal and neonatal outcomes were compared between groups both for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…However, the inclusion and exclusion criteria used in our study do not allow us to generalize our findings to every pregnancy circumstance. Further studies, including twin pregnancies and premature deliveries, must be conducted to confirm our results in those populations 13,16 . Moreover, external validity should be discussed because we worked with a French population sample.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, the inclusion and exclusion criteria used in our study do not allow us to generalize our findings to every pregnancy circumstance. Further studies, including twin pregnancies and premature deliveries, must be conducted to confirm our results in those populations 13,16 . Moreover, external validity should be discussed because we worked with a French population sample.…”
Section: Discussionmentioning
confidence: 85%
“…These analyses make an important contribution to the literature because of the sparse information concerning predictive scores in this specific population in addition to the well-known higher risk of induction failure. 12,13 Another key highlight of our work is that we compared the current scores with each other instead of proposing a new score. 11,14,15 However, the inclusion and exclusion criteria used in our study do not allow us to generalize our findings to every pregnancy circumstance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that there is an increased risk of perinatal mortality and morbidity when a twin pregnancy continues beyond 37 weeks, and that lower risks are seen when twins are born between 36 and 38 weeks [ 31 , 32 ]. Our study findings of our study may indicate the higher indication (preference) of a CS as a type of delivery for multiple pregnancies, although the safest method for delivering twins at term, or close to term, remains a controversial issue [ 33 35 ].…”
Section: Discussionmentioning
confidence: 94%